Task-sharing or public finance for the expansion of surgical access in rural Ethiopia: an extended cost-effectiveness analysis. Issue 6 (29th December 2015) - Shrime, Mark G; Verguet, Stéphane; Johansson, Kjell Arne; Desalegn, Dawit; Jamison, Dean T; Kruk, Margaret E
Abstract : Despite a high burden of surgical disease, access to surgical services in low- and middle-income countries is often limited. In line with the World Health Organization's current focus on universal health coverage and equitable access to care, we examined how policies to expand access to surgery in rural Ethiopia would impact health, impoverishment and equity. An extended cost-effectiveness analysis was performed. Deterministic and stochastic models of surgery in rural Ethiopia were constructed, utilizing pooled estimates of costs and probabilities from national surveys and published literature. Model calibration and validation were performed against published estimates, with sensitivity analyses on model assumptions to check for robustness. Outcomes of interest were the number of deaths averted, the number of cases of poverty averted and the number of cases of catastrophic expenditure averted for each policy, divided across wealth quintiles. Health benefits, financial risk protection and equity appear to be in tension in the expansion of access to surgical care in rural Ethiopia. Health benefits from each of the examined policies accrued primarily to the poor. However, without travel vouchers, many policies also induced impoverishment in the poor while providing financial risk protection to the rich, calling into question the equitable distribution of benefits by these policies. Adding travel vouchers removed the impoverishing effects of a policy but decreased the health benefit that could be bought per dollar spent. These results were robust to sensitivity analyses.